2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.260550
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Support Vector Machine-based Classification of Heart Rate Signals

Abstract: In this study, we discuss the use of support vector machine (SVM) learning to classify heart rate signals. Each signal is represented by an attribute vector containing a set of statistical measures for the respective signal. At first, the SVM classifier is trained by data (attribute vectors) with known ground truth. Then, the classifier learnt parameters can be used for the categorization of new signals not belonging to the training set. We have experimented with both real and artificial signals and the SVM cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In [17], SVM were used to classify and compare the breathing patterns of patients undergoing weaning trials. The authors of [18] employed this algorithm to classify the heart rate signal. They obtained the reading from three distinct sets of individuals: the young, teenagers, and elders.…”
Section: Naïve Bayes (Nb)mentioning
confidence: 99%
“…In [17], SVM were used to classify and compare the breathing patterns of patients undergoing weaning trials. The authors of [18] employed this algorithm to classify the heart rate signal. They obtained the reading from three distinct sets of individuals: the young, teenagers, and elders.…”
Section: Naïve Bayes (Nb)mentioning
confidence: 99%
“…Osowski et al [61] HOS, Hermite expansion Arrhythmia detection Kampouraki et al [62] HRV time domain features HRV classification Mohebbi et al [63] RR time and frequency features AF detection Melgani et al [64] Morphology + timing Arrhythmia detection Mehta et al [65] Entropy QRS detection Kostka et al [66] Wavelet AF detection Mehta et al [72] ECG slope P T detection separability among classes. This implies the maximization of a cost-function based on eigenvectors of S w -1 S b .…”
Section: Reference Features Applicationmentioning
confidence: 99%
“…For HRV analysis, Kampouraki et al [62] used the Fantasia Database from Physionet (see Section 10) for classifying young and elderly people's HRV while watching a Disney film, through conventional HRV features (section 6). Kampouraki et al [62] used SVM for RR series classification and found that SVM performed better than ANN. They used conventional statistical HRV features, autocorrelation, Shannon entropy, autoregressive coefficients and discrete wavelet transform.…”
Section: Heart Rate Variability Analysismentioning
confidence: 99%
See 2 more Smart Citations